2015
DOI: 10.1186/s12886-015-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Inferior retinotomy and silicone oil tamponade for recurrent inferior retinal detachment and grade C PVR in eyes previously treated with pars plana vitrectomy or scleral buckle

Abstract: BackgroundOne of the most challenging problems in vitro-retinal surgery is the recurrence of retinal detachment in the context of high-grade proliferative vitreoretinopathy (PVR). The aim of our retrospective study was to assess the surgical outcomes of pars plana vitrectomy, 180° inferior retinotomy and silicone oil tamponade combined with phacoemulsification and IOL implantation for recurrent inferior retinal detachment with grade C PVR in phakic eyes. The study was carried out at tertiary referral centre - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
5
22
0
1
Order By: Relevance
“…Also, the final anatomical success was more for the buckle group (95.2%) than the retinectomy group (90%) with no statistical significant difference (p = 0.49). Similar to our results but in recurrent cases, Mancino et al showed that successful attachment for cases with recurrent RD after vitrectomy using inferior retinectomy was higher in cases with previous buckle than cases with previous vitrectomy [18].…”
Section: Discussionsupporting
confidence: 91%
“…Also, the final anatomical success was more for the buckle group (95.2%) than the retinectomy group (90%) with no statistical significant difference (p = 0.49). Similar to our results but in recurrent cases, Mancino et al showed that successful attachment for cases with recurrent RD after vitrectomy using inferior retinectomy was higher in cases with previous buckle than cases with previous vitrectomy [18].…”
Section: Discussionsupporting
confidence: 91%
“…The final anatomical success of vitrectomy for recurrent and complicated retinal detachment cases was reported as 93% by Quiram et al, 80% by Pournaras et al, 90-100% by Mancino et al, around 70% by Wei et al and 65% by Karakaya et al in previous studies. [9][10][11][12] Our final anatomical success rate was similar to the studies reported above. Pournaras et al evaluated the anatomical and functional outcomes for recurrent retinal detachment surgery in a retrospective study, which included 70 patients.…”
Section: Discussionsupporting
confidence: 89%
“…The most important reason for primary anatomical failure for RD surgery is PVR and it occurs in approximately 5-10% of the patients. [9][10] The primary success rate of vitrectomy in patients with recurrent RD with PVR was reported between as low as 14% to as high as 80%. [10] The final anatomical success rate was increased by 10%…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports about surgery outcomes from complex retinal detachment surgery using heavy SO have shown success rates ranging between 39 and 92%, with different number of surgeries being required and a high incidence of complications being reported [42, 4649]. Mancino et al recently reported 100 and 90.4% success rate of vitrectomy with inferior 180° peripheral retinectomy and SO tamponade in subgroups of patients with recurent retinal detachment and PVR grade C after failed primary scleral buckle surgery and PPV, respectively [50]. …”
Section: Discussionmentioning
confidence: 99%